Bristol's trade with Ireland and the continent 1503 - 1601 ; the evidence of the exchequer (Four Courts Press, 2009)
The eleven Bristol 'particular' accounts and port books reproduced in this volume were chosen to assist the re-evaluation of the economic development of southern Ireland before and during the Nine Years War (1594-1603).